Sensores nanoestruturados compostos por nanofibras de dióxido de titânio modificadas com polímeros condutores visando monitoramento de compostos orgânicos voláteis - Conti, Patrick Pires (Universidade Federal de São Carlos, 2020)
The growth of urbanization and anthropogenic activities have been increasing the emission of polluting gases in the atmosphere. Considering the high toxicity of some of these gases, it becomes necessary to develop new sensors that allow the monitoring of gases with high sensitivity, low cost and selectivity. In this scenario, the use of chemical sensors has been proven to be an efficient strategy. Ceramic and polymeric materials have been widely explored by science and industry for the development of sensors, given their interesting electrical and optical properties. However, in order to optimize and improve the performance of these devices, hybrid materials have been studied due to the synergistic effect between the constituent phases. Thus, this project proposes the development of a electronic nose sensor based on hybrid platforms of ceramic nanomaterials and conductive polymers for the monitoring of VOCs. TiO2 particles were obtained through the sol-gel synthesis route and showed spherical morphology, crystalline anatase phase, without impurities and with an average diameter of 23 ± 10 nm. The TiO2 fibers were obtained using the electrospinning technique, which showed homogeneity in the distribution, diameter of 111 ± 16 nm and length of some micrometer. Through Transmission Electron Microscopy it was noted that coalesced and compacted nanoparticles constituted the fibers’ structures. Platforms based on TiO2 nanocomposites with different concentrations of poly(3,4-ethylenedioxythiophene):sulfonated polystyrene (PEDOT: PSS), polypyrrole (PPY) and polystyrene sulfonated (PSS) were produced. Films of these nanocomposites were deposited on interdigitated electrodes to make the sensing units of the electronic nose, aiming at monitoring 600 ppm acetone, 600 ppm ethanol and 160 ppm formaldehyde, through impedance spectroscopy measurements. By analyzing the e-nose performance with the aid of PCA statistical tool, it is noticed the system performed well in discriminating analytes with data variance of 97.93%, thus indicating good performance of the electronic nose for monitoring VOCs.
Nanostructured sensors composed of titanium dioxide nanofibers modified with conductive polymers for monitoring volatile organic compounds
Keywords: Nariz eletrônico; Compostos orgânicos voláteis; Óxido de titânio; Sensores; Polímeros condutores; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA